2016
DOI: 10.1111/aogs.12897
|View full text |Cite
|
Sign up to set email alerts
|

Blame and guilt – a mixed methods study of obstetricians' and midwives' experiences and existential considerations after involvement in traumatic childbirth

Abstract: Introduction. When complications arise in the delivery room, midwives and obstetricians operate at the interface of life and death, and in rare cases the infant or the mother suffers severe and possibly fatal injuries related to the birth. This descriptive study investigated the numbers and proportions of obstetricians and midwives involved in such traumatic childbirth and explored their experiences with guilt, blame, shame and existential concerns. Material and methods. A mixed methods study comprising a nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
75
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 28 publications
8
75
1
4
Order By: Relevance
“…Midwives and nurses witnessing such events are predisposed to a higher degree of emotional and psychological trauma (Schroder, Jorgensen, Lamont, & Hvidt, ; Sheen et al., ; Sheen, Spiby, & Slade, ). In a recent survey of Australian midwives, more than two‐thirds of respondents (67.2%) reported having witnessed a traumatic birth, with 74.8% experiencing feelings of horror and 65.3% guilt (Leinweber, Creedy, Rowe, & Gamble, ).…”
Section: Introductionmentioning
confidence: 99%
“…Midwives and nurses witnessing such events are predisposed to a higher degree of emotional and psychological trauma (Schroder, Jorgensen, Lamont, & Hvidt, ; Sheen et al., ; Sheen, Spiby, & Slade, ). In a recent survey of Australian midwives, more than two‐thirds of respondents (67.2%) reported having witnessed a traumatic birth, with 74.8% experiencing feelings of horror and 65.3% guilt (Leinweber, Creedy, Rowe, & Gamble, ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some midwives can become self-judgemental when targeting the high standards they aspire to, be left to their own devices when dealing with the emotional labour of caring for women, or left to cope with their distress by swallowing their emotions in cultures of service and sacrifice (Davies, Coldridge 2015, Beaumont, Durkin et al 2016, Schrøder, Jørgensen et al 2016. Should midwives continue to use persistence and avoidance as maladaptive coping strategies for dealing with distress, their dysfunctional endurance may not enable them to recognise ill health in either themselves or their colleagues.…”
Section: Introductionmentioning
confidence: 99%
“…In a national study on how Danish midwives and obstetricians ( n = 1237) experience adverse events in childbirth, we found that fear of being blamed by the patient, clinical peers or through official complaints was of considerable concern to obstetricians and midwives, although few had experiences of such blame. Feelings of guilt were reported by 50% of the respondents, which in the interview study was described as a psychological burden, even in cases where no blame was attached . These reports of feeling guilt without being at fault or experiencing blame indicate that a blame‐free culture per se does not relieve the HCPs of distress and guilt feelings that they may experience following an adverse event.…”
Section: Struggling With Guilt Even When There Is No Blamementioning
confidence: 84%
“…Feelings of guilt were reported by 50% of the respondents, which in the interview study was described as a psychological burden, even in cases where no blame was attached. 5 Commentary that a blame-free culture per se does not relieve the HCPs of distress and guilt feelings that they may experience following an adverse event. Zinck Pedersen 6 characterises the current Danish safety programme as training HCPs in 'appropriate' blame-free attitudes and in approaching adverse events as systemic.…”
Section: Struggling With Guilt Even When There Is No Blamementioning
confidence: 99%